2022
DOI: 10.3389/fmicb.2022.935884
|View full text |Cite
|
Sign up to set email alerts
|

A buffalo rumen-derived probiotic (SN-6) could effectively increase simmental growth performance by regulating fecal microbiota and metabolism

Abstract: Microorganisms play a key role in ruminal digestion, some of which can be used as probiotics to promote growth in ruminants. However, which potential bacteria are responsible for ruminant growth and how they potentiate the basic mechanism is unclear. In this study, three bacterial strains, Bacillus pumilus (SN-3), Bacillus paralicheniformis (SN-6), and Bacillus altitudinis (SN-20) with multiple digestive enzymes were isolated from the rumen of healthy buffaloes. Among these strains, SN-6 secreted cellulase, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
1
0
0
Order By: Relevance
“…Recent studies have shown that a strain of B. paralicheniformis, SN-6, could enhance the host's amino acid metabolism (mainly tryptophan metabolism) and lipid metabolism pathways and serve as a probiotic additive for animals [47]. This result corresponded with the GO enrichment analysis of B. paralicheniformis.…”
Section: Comparative Pangenomes and Enrichment Analysis Facilitated R...supporting
confidence: 60%
“…Recent studies have shown that a strain of B. paralicheniformis, SN-6, could enhance the host's amino acid metabolism (mainly tryptophan metabolism) and lipid metabolism pathways and serve as a probiotic additive for animals [47]. This result corresponded with the GO enrichment analysis of B. paralicheniformis.…”
Section: Comparative Pangenomes and Enrichment Analysis Facilitated R...supporting
confidence: 60%